Pengaruh Edukasi Tentang Protokol Kesehatan Terhadap Pengetahuan dan Sikap Pencegahan Penularan Covid-19 pada Anak Usia 10-12 Tahun - Sambo, Mery; Beda, Nikodemus S.; Odilaricha, Yolanda Christiana; Marampa, Litwina (Nursing Care and Health Technology Journal (NCHAT), 2021)
The lack of knowledge and attitudes of children towards health protocols (washing hands, wearing mask, physical distancing) as an effort to prevent COVID-19 is the main factor that causes the incidence of COVID-19 in children to continue and is increasing. So, there is a need for education on health protocols (washing hands, wearing mask, physical distancing) so that children can avoid COVID-19. The purpose of this study was to determine the effect of health protocol education on knowledge and attitudes to prevent COVID-19 transmission in children. This study used a pre-experimental study with a one group pre test-post test design approach. The population in the study was 400 children and the research sample was 78 children aged 10-12 years, which were taken using stratified random sampling technique. The result of the study were analyzed using the Wilcoxon statistical test with a significance level of ?=0,05, the value of p=0,000 was obtained, this shows that there is an effect of health protocol education on knowledge and atitudes to prevent COVID-19 transmission in children aged 10-12 years at Frater Bakti Luhur Elementary School. Providing education has a great impact on increasing knowledge and attitudes.